SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN BONUS KARYAWAN MENGGUNAKAN METODE AHP - Nuriadi Manurung (Universitas Asahan, 2017)
Abstract - In each company, agency, organization or business entity will provide salary as compensation for the work of an employee, in addition to providing basic salary to employees, each agency often provides salary bonuses in addition to basic salary to spur the performance and work productivity of its employees. As for the way used is to do the selection of employees according to the criteria by the leader, the salary bonus is given together with the salary each month. Criteria for determining employees who have priority to get salary bonuses include responsibility, work attitude, and honesty. Besides still using a conventional system, the closeness of the leader and employees often results in decisions that are different from the right thing. This causes the results of the decision to be inappropriate. The problem in this research is how to build a support system the decision to use the AHP method to help company leaders in determining employees who are entitled to receive bonuses. Keywords - Employee Bonuses, AHP, Decision Supporters.